PENGARUH KUALITAS LAYANAN TERHADAP LOYALITAS YANG DIMEDIASI OLEH KEPUASAN PELAYANAN - Masdiah, Novita; Graha, Andi Nu; Sedyastuti, Kristina (Jurnal Manejemen, Akuntansi dan Pendidikan, 2024)
ABSTRACT Pondok Pesantren is a traditional education where students live together and study under the guidance of teachers who are better known as kiai and have dormitories for students to stay. Since the beginning of entering the Islamic boarding school, the attitude of the students must be awakened, so that in this way the ideals of the students that have been awakened since the beginning are stronger and easier to realize. Based on the results of a survey in the field, the loyal and obedient attitude of a santri when entering an Islamic boarding school begins to be developed, this attitude emerges and continues to be honed for independent learning when away from parents, to deepen religious knowledge, seek peace of mind, and seek blessings from kyai and many more. To determine the effect of service quality (X) on loyalty (Y) at the Bihaaru Bahri Islamic Boarding School As'ali Fadlaailir Rahmah, Turen District, Malang Regency. To determine the effect of service quality (X) on service satisfaction (Z) at the Bihaaru Bahri Islamic Boarding School As'ali Fadlaailir Rahmah, Turen District, Malang Regency. To determine the effect of service quality (X) on loyalty (Y) which is mediated by service satisfaction (Z) of Bihaaru Bahri As'ali Fadlaailir Rahmah Islamic Boarding School caregivers, Turen District, Malang Regency. The results of the analysis show that there is a significant influence of service quality (X) on student loyalty (Y) at the Bihaaru Bahri As'ali Fadlaailir Rahmah Islamic Boarding School, Turen District, Malang Regency. There is a significant influence between service quality (X) on service satisfaction (Z) at the Bihaaru Bahri Islamic Boarding School As'ali Fadlaailir Rahmah, Turen District, Malang Regency. There is a significant effect of service quality (X) on student loyalty (Y) which is mediated by service satisfaction (Z) of Bihaaru Bahri Islamic Boarding School caregivers As'ali Fadlaailir Rahmah Malang Regency Keywords: quality, satisfaction, loyalty of students